Presidential Support in Latin America 2010-2012: Economic Vote and Political Preferences - Cabezas, José M. (Política. Revista de Ciencia Política, 2015)
The study of the economic vote focused primarily in the States and industrialized democracies. Using the evidence from 24 Latin American countries for the years 2010 and 2012. I analyzed economic vote patterns. Both individuals and macroeconomic performance indicators allowed me to prove that the Latin American electorate presents some patterns of similarities with the previous evidence, especially when considering individuals characteristics such as Party Identification and perceptions about the economy. But on the other hand the Latin American electorate behaves counterintuitively with all the previous evidence when considering the macroeconomic performance.